New Indazole Compounds Derived from Ethyl-4-Hydroxy-4'-Substituted-Cyclohexen- 6- One- Carboxylate: Synthesis and Biological Activity - Jumbad H. Tomma (Journal of Global Pharma Technology, 2018)
The work involves synthesis of new compounds: Schiff bases [VIII] a-c, pyrazoles[V]a-c, starting with chalcones [I]a-c. 4- Hydroxyacetophenone was reacted with benzaldehyde , anysaldehyde and tolyaldehyde in basic medium to give three chalcones[I]a-c compounds by Claisen-Schemidt reaction, the chalcones[I]a-c were reacted with ethylacetoacetate in basic medium to get new compounds[II]a-c, which were reacted with ethylchloroacetate in basic medium to obtained ester compounds [III]a-c. The condensation of esters[III]a-c with hydrazine hydrate led to produce accurse pounding acid hydrazides [IV]a-c , the reaction of acid hydrazides [IV]a-c with ethyl aceto acetate led to formation pyrazoles[V]a-c , which were reacted with acetyl chloride in basic medium to get compounds [VI]a-c the later compound reacted with phenyl hydrazine or 2,4 di nitrophenyl hydrazine to led compounds [VII] a-f . On the other hand, acid hydrazides [IV] a-c reacted with 4- substituted benzaldehyde to form Schiff bases [VIII] a-I. The synthesized compounds were characterized by FTIR, 1HNMR and Mass spectroscopy (of some of them).Keywords: Chalcones, Acid hydrazide, Pyrazole, Indazoles, Schiff bases.